ANALISIS PROFITABILITAS, LIKUIDITAS DAN NILAI PASAR TERHADAP HARGA SAHAM PADA SEKTOR PERTANIAN YANG TERDAFTAR DI BEI - Iskandar, Otto; Tipa, Handra (LPPM Universitas Putera Batam, 2021)
In general, every company always improves its company's performance to make it better so that investors do not hesitate to invest in the company, which of course will affect the company's stock price. An investor who wants to invest, of course, must have a mature strategy and knowledge so that the investment can be profitable, such as analyzing company financial statements using several commonly used financial ratios. This research was conducted to see whether there is a significant effect on profitability, liquidity and stock market value, especially companies operating in the agricultural sector. The population in this study consisted of 24 companies and the study used techniques and samples in the form of purposive sampling and showed that the samples that could be used consisted of 7 companies. The research results obtained from the T test results show a significant effect on market value and there is no significant effect. While the F test shows that the third independent variable simultaneously has a significant effect on stock prices. And the results of the coefficient of determination R2 obtained a percentage of 89.9% and the remaining proportion of 10.1% from other variables not contained in this research variable.